2012
DOI: 10.1016/j.chemosphere.2012.05.008
|View full text |Cite
|
Sign up to set email alerts
|

The effects of biochars from rice residue on the formation of iron plaque and the accumulation of Cd, Zn, Pb, As in rice (Oryza sativa L.) seedlings

Abstract: h i g h l i g h t s" Rice biochar reduced Cd, Zn and Pb transport to rice shoots, though increased As. " Biochars derived from rice straw were more influential than from bran and husk. " Mechanisms for these effects were identified. " Biochar increased iron plaque formation, and its capacity to retain Cd and Pb. " Biochar also influenced the soil pore water solubility of Cd, Zn, Pb and As. A historically multi-metal contaminated soil was amended with biochars produced from different parts of rice plants (straw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 268 publications
(84 citation statements)
references
References 38 publications
7
75
1
1
Order By: Relevance
“…This demonstrates that high-level biochar can inhibit the transportation of Cd from the underground part to the aboveground part, and accordingly reduce the accumulation of Cd in the aboveground part of cabbage. Similar results were also addressed by Zhang et al [20] and Zheng et al [23]. However, in some other studies, Cd bioaccumulation increased after applying biochar [11,19].…”
Section: Effect Of Biochar On Cabbage Biomass and CD Content In Cabbagesupporting
confidence: 79%
“…This demonstrates that high-level biochar can inhibit the transportation of Cd from the underground part to the aboveground part, and accordingly reduce the accumulation of Cd in the aboveground part of cabbage. Similar results were also addressed by Zhang et al [20] and Zheng et al [23]. However, in some other studies, Cd bioaccumulation increased after applying biochar [11,19].…”
Section: Effect Of Biochar On Cabbage Biomass and CD Content In Cabbagesupporting
confidence: 79%
“…Finally, there are also other studies showing that metal mobility is reduced in the presence of biochar due to adsorption on the biochar surface (especially on carboxylic and phenolic groups; Uchimiya et al 2011a, b). On the other hand, a probable increase in the silicon (Si) concentration of soil solution after biochar addition may also contribute to metal immobilization via the formation of silicate precipitates (Houben et al 2014;Zheng et al 2012;Gu et al 2011). A significant increase in Si concentration of soil pore water after biochar (made from rice straw) addition was obtained in our recent study ).…”
Section: Discussionmentioning
confidence: 49%
“…Decreases in Cd, Zn, and Pb concentrations and an increase in As concentration in rice plants grown in a multi-element contaminated soil under flooded conditions after biochar addition were also observed in previous studies by the authors . Studies showed that heavy metals were immobilized and As was mobilized in soils after biochar addition (Beesley et al 2010;Zheng et al 2012). Concentrations of Cd and Zn in soil pore water decreased significantly, whereas that of As increased markedly in a multi-element polluted soil amended with biochar under various soil moisture conditions (Beesley et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…"Biochars for metals in soil," BioResources 8(4), 5965-5982. 5966 2010; Zheng et al 2012). Concentrations of Cd and Zn in soil pore water decreased significantly, whereas that of As increased markedly in a multi-element polluted soil amended with biochar under various soil moisture conditions (Beesley et al 2010).…”
mentioning
confidence: 99%